Penerapan Relaksasi Nafas Dalam Untuk Menurunkan Ansietas Pada Ibu Hamil Trimester III Dimasa Pandemi COVID-19 - Anggi Novita Dwi Yuliyati; Heny prasetyorini (Jurnal Manajemen Asuhan Keperawatan, 2022)
Pregnancy is a time of joy and anticipation. However, it can become anxiety and become a concern. Common problems experienced by women during pregnancy are anxiety and stress. Third trimester of pregnancy is the period of the last three months or the last third of the gestation period. The third trimester is the gestation period from the seventh to the ninth month (28-40 weeks). The gestation period starts from conception to the birth of the fetus. Normal length of pregnancy is 280 days (40 weeks or 9 months 7 days) calculated from the first day of the last menstruation. Anxiety (anxiety/anxiety) is a natural feeling disorder characterized by feelings of fear or worry that are deep and ongoing, do not experience disturbances in assessing reality, personality is still intact (no splitting of personality), behavior can be disrupted but is still in progress. normal limits. One of the management actions to reduce anxiety is deep breathing relaxation therapy. The purpose of this case study is to reduce anxiety in third trimester pregnant women during the COVID-19 pandemic. The case study method is in the form of a one grub pretest posttest design. The subjects of this study were 2 patients with third trimester pregnant women. The results of the study showed that there was a change in the level of anxiety from mild anxiety to no anxiety after being given the Deep Breathing Relaxation intervention for 3 days so it is hoped that the patient and the patient's family can take Deep Breathing Relaxation to reduce anxiety levels in third trimester pregnant women.